Revisiting Stock Market Integration Pre-Post Subprime Mortgage Crisis: Insight From BRIC Countries - Chin-Hong Puah; Rayenda Khresna Brahmana; Kai-Hung Wong (Economics and Finance in Indonesia, 2015)
AbstractThis study revisits the long-run relationships and short-run dynamic causal linkages among BRIC stock market, with the particular attention to the 2008 subprime mortgage crisis. Extending related empirical studies, comparative analyses of pre-crisis, and post-crisis periods were conducted to comprehensively evaluate how stock market integration was affected by financial crises. In general, after employing cointegration test and VAR test, the results reveal the increase of stock market integration in BRICs after the subprime crisis. The evidence also found that China stock market is the most influential among the BRICs, in which China stock market has the ability to Granger cause the other three BRICs member countries. An important implication of our findings is that the degree of integration among countries tends to change over time, especially around periods marked by financial crises. AbstrakPenelitian ini mengkaji ulang hubungan jangka panjang dan hubungan kausal dinamis jangka pendek antara pasar modal negara-negara BRIC, terutama pada saat krisis subprime mortgage 2008. Pengayaan studi empiris yang terkait dan analisa perbandingan sebelum-sesudah krisis dilakukan untuk mengevaluasi secara komprehensif tentang bagaimana krisis keuangan memengaruhi integrasi pasar modal. Secara umum, setelah menggunakan uji kointegrasi dan uji VAR, hasil penelitian ini memperlihatkan peningkatan integrasi pasar modal di negara-negara BRIC setelah terjadinya krisis subprime. Penelitian ini juga membuktikan bahwa pasar modal Cina adalah pasar yang paling berpengaruh di antara negara BRIC, di mana pasar modal Cina memiliki kemampuan untuk memengaruhi secara Granger Causality tiga negara anggota BRIC lainnya. Implikasi penting dari temuan kami adalah bahwa tingkat integrasi antara negara-negara cenderung berubah dari waktu ke waktu, terutama sekitar periode yang ditandai oleh krisis keuangan.Kata kunci: Integrasi Pasar; Subprime Mortgage; Krisis Keuangan; BRICJEL classifications: F15; G15; G21; C32